Temple Diplomacy, Sacred Rites, and Overseas Chinese During the Reign of Song Emperor Zhenzong (997–1022) - Gregory Sattler (Religions)
Throughout most of Chinese history, leaders viewed the migration and movement of their subjects beyond state borders as a symptom of poor governance. As a result, record keepers generally avoided addressing the topic of Chinese people traveling or residing overseas. There is, however, an exceptional moment in Chinese history that provides valuable insight into the early establishment of Chinese communities abroad. Facing political pressure after signing a humiliating peace treaty with foreign adversaries in 1005, the Song dynasty emperor Zhenzong (968–1022, r. 997–1022) utilized unconventional forms of religious diplomacy and revived ancient rites to shore up support for his rule. The Feng and Shan rites were the highest level of sacrifice that an emperor could undertake, and they were only carried out by several emperors prior to Zhenzong’s reign. One of the requirements of this complex ritual was for the sovereign to attract foreign peoples from afar by his virtuous character, and so Zhenzong’s reign witnessed major initiatives to attract foreign envoys from states such as Srivijaya (Sumatra), Dai Viet (northern Vietnam), Japan, and India. Zhenzong’s reign also incorporated forms of diplomacy that originated in South and Southeast Asia, namely, the construction of temples in foreign states to enhance his spiritual authority. This essay will demonstrate that Emperor Zhenzong relied on Chinese merchants residing overseas to work with foreign leaders to coordinate the participation of foreign emissaries in such forms of temple diplomacy and in the Feng and Shan sacrifices. The significance of these events brought the activities of Chinese people trading and residing overseas to the attention of the Song court and its chroniclers, and as a result, we are left with the earliest indications of Chinese communities abroad in official Chinese histories.